Storage Insects on Yam Chips and Their Traditional Management in Northern Benin - Y. L. Loko; A. Dansi; M. Tamo; A. H. Bokonon-Ganta; P. Assogba; M. Dansi; R. Vodouhè; A. Akoegninou; A. Sanni (The Scientific World Journal)
Twenty-five villages of Northern Benin were surveyed to identify the constraints of yam chips production, assess the diversity of storage insects on yam chips, and document farmers' perception of their impacts on the stocks and their traditional management practices. Damages due to storage insects (63.9% of responses) and insufficiency of insect-resistant varieties (16.7% of responses) were the major constraints of yam chips production. Twelve insect pest species were identified among which Dinoderus porcellus Lesne (Coleoptera, Bostrichidae) was by far the most important and the most distributed (97.44% of the samples). Three predators (Teretrius nigrescens Lewis, Xylocoris flavipes Reuter, and Alloeocranum biannulipes Montrouzier & Signoret) and one parasitoid (Dinarmus basalis Rondani) all Coleoptera, Bostrichidae were also identified. The most important traditional practices used to control or prevent insect attack in yam chips were documented and the producers' preference criteria for yam cultivars used to produce chips were identified and prioritized. To further promote the production of yam chips, diversification of insect-resistant yam varieties, conception, and use of health-protective natural insecticides and popularization of modern storage structures were proposed.